Myxopapillary ependymomas in children: clinical, morphological characteristics and treatment outcomes - Igor N. Kasich; A. E. Druy; A. V. Protsvetkina; A. V. Tarakanova; A. V. Artyomov; K. F. Boiko; V. V. Gornostaev; E. A. Salnikova; M. A. Zaytseva; A. E. Sysoev; A. A. Merishavyan; M. M. Koldasheva; et al. (Pediatric Hematology/Oncology and Immunopathology, 2026)
Introduction. Myxopapillary ependymoma (MPE) is a rare ependymal neoplasm arising predominantly from the conus medullaris, cauda equina, and filum terminale. In the pediatric population, MPE accounts for less than 10% of all ependymomas and approximately 1–2% of all primary central nervous system tumors. Compared to adults, pediatric MPE displays a more aggressive clinical course, with higher rates of leptomeningeal dissemination at diagnosis (reported in up to 35–58% of cases in some series) and higher rates of local and metastatic recurrence following surgical treatment. In accordance with the 2021 World Health Organization Classification of Central Nervous System Tumors, MPE has been reclassified as a Grade 2 neoplasm. Large pediatric cohorts with concurrent analysis of clinical and morphological features and treatment outcomes remain scarce, and national data from Russian institutions are virtually absent from the international literature. The aim of this study was to analyze the clinical and morphological characteristics of pediatric MPE and to evaluate the impact of extent of surgical resection and radiation therapy (RT) on disease outcomes. Materials and methods. This retrospective study included 49 patients under 18 years of age with histologically confirmed MPE at the Dmitry Rogachev National Medical Research Center of Pediatric Hematology, Oncology and Immunology (Moscow) between 2013 and 2025. Parameters analyzed included patient demographics, tumor localization, metastatic staging per Chang classification (M0–M3), extent of surgical resection, use of RT. The primary endpoint was event-free survival (EFS), defined as time from diagnosis to disease progression or relapse. A morphological sub-analysis was performed in 28 patients with available archival histological material, evaluating candidate anaplasia features: high cellularity, mucin reduction, high mitotic activity (≥5 mitoses per high-power field at ×400 or Ki-67 ≥10%), endothelial proliferation, spontaneous necrosis, and heterogeneous GFAP expression. A composite anaplasia index was calculated. Statistical analyses were performed in R 4.5.2 using Kaplan–Meier estimation, log-rank testing, and multivariate Cox proportional-hazards regression. Results. Of 49 patients, 57.1% were male and the median age at diagnosis was 12.8 years (range 5.8–18.0). The predominant tumor location was the lumbosacral spinal cord (85.7%). Metastatic dissemination at diagnosis was identified in 8/49 (16.3%) patients. Gross total resection was achieved in 28/49 (57.1%) patients. RT was administered to 23/49 (46.9%) patients. At the time of analysis, all 49 patients were alive (overall survival – 100%), with a median follow-up of 4.2 years. Disease progression or relapse occurred in 12/49 (24.5%) patients. The 3- and 5-year EFS for the entire cohort were 77.6% and 69.4%, respectively. On multivariate Cox analysis, adjuvant RT was an independent statistically significant predictor of EFS (hazard ratio 0.05; 95% confidence interval 0.01–0.44; p = 0.007). The greatest benefit from RT was observed in patients with incomplete resection: 5-year EFS increased from 22.2% with surgery alone to 66.7% with the addition of RT. In contrast, patients achieving R0 resection without RT already demonstrated a favorable 5-year EFS of 75.6%. In the morphological subgroup, a composite anaplasia index ≥2 was significantly associated with inferior EFS: 44.0% vs. 81.0% (log-rank p = 0.046; adjusted hazard ratio 4.44; 95% confidence interval 1.04–19.0; p = 0.044). Conclusion. Pediatric MPE is characterized by excellent overall survival but heterogeneous EFS outcomes determined primarily by extent of resection and adjuvant RT. A risk-adapted strategy – reserving RT for patients with residual disease – is supported by the results of this study and is consistent with EANO guidelines for spinal ependymomas. Routine RT following gross total resection appears unnecessary, given the well-documented long-term radiation toxicity in growing children. The proposed composite morphological anaplasia index represents a promising tool for additional risk stratification in pediatric MPE, pending validation in larger, prospective, and preferably multicenter cohorts.